Artificial Reef Deployment in North Bali, Indonesia: An Innovative Strategy to Rebuild Reef Ecosystem in Climate Change Affected Area - P., Anju; P. K., Sariga; Sekharan N., Mini; Ghosh, Swagat; Balachandran, Nidhin; Reksodihardjo-Lilley , Gayatri (Fishery Technology, 2023)
Cyanide fishing, ghost fishing, explosive fishing and other destructive practices are already impacting the reefs and the scenario may get worsened by climate change. As a result of climate change, coral bleaching and coastal erosion is taking place, because of the drastic change in the oceanographic conditions, such as currents, salinity, surface water temperature and waves. Increase in temperature and salinity are particularly harmful to corals, marine fish, and benthic organisms associated with reefs. In order to address the impacts of climate change, it is necessary to develop adaptive measures. As a means of restoring reef ecosystems deteriorated by exploitation, natural calamities and climate change, artificial reef deployment is being investigated as an adaptive strategy. As part of this study, artificial reefs were deployed in the Pacific Ocean in North Bali, Indonesia in assistance with the reef restoration activities by the non-governmental organization LINI (Yayasan Alam Indonesia Lestari) Aquaculture and Training Centre (LATC). Three types of artificial reefs were constructed (Roti buaya, Shrimp pots and Fish domes). Fish and corals were  less abundant in places where these structures were deployed. All deployed structures were found to be thriving with coral and fish species after deployment. The deployment strategy of artificial reefs was effective in creating microhabitats.